2020
DOI: 10.1007/s41825-020-00028-9
|View full text |Cite
|
Sign up to set email alerts
|

How solar home systems temporally stimulate increasing power demands in rural households of Sub-Saharan Africa

Abstract: Small solar home systems (SHS) have emerged as potential alternatives to grid electrifications, enabling households to make modest investments into their power systems, and to modify those systems according to their changing economic circumstances and power demands. Study shows that introduction to basic electricity access temporally stimulates increasing power demands in rural households, leading to eventual installations of larger systems that can power more electric appliances. Specifically, study shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Access to, and initial consumption of electricity has been shown to lead to increases in consumption over time, as users purchase more appliances (if affordable) [32]. This is in line with the study by Opiyo [33], which demonstrated that rural households in Kenya, upon realising the socioeconomic benefits of their basic electricity access from SHS, began to desire more high-powered appliances such as televisions and cooling fans. However, some researchers, such as Lee et al [34] and Stojanovski et al [20], have observed that while rural households purchased these appliances to benefit from the services they provide, they could not be accommodated by their SHSs due to their relatively small energy capacity, and hence these appliances were unusable.…”
Section: Figuresupporting
confidence: 71%
See 1 more Smart Citation
“…Access to, and initial consumption of electricity has been shown to lead to increases in consumption over time, as users purchase more appliances (if affordable) [32]. This is in line with the study by Opiyo [33], which demonstrated that rural households in Kenya, upon realising the socioeconomic benefits of their basic electricity access from SHS, began to desire more high-powered appliances such as televisions and cooling fans. However, some researchers, such as Lee et al [34] and Stojanovski et al [20], have observed that while rural households purchased these appliances to benefit from the services they provide, they could not be accommodated by their SHSs due to their relatively small energy capacity, and hence these appliances were unusable.…”
Section: Figuresupporting
confidence: 71%
“…SHSs are often seen as a means to get households onto the modern energy ladder [33,44,45]. However, the results show that for many it was a less desirable substitute for a grid-based service.…”
Section: Discussionmentioning
confidence: 99%
“…Azuri Technologies, for instance, has introduced innovative pay-as-you-go solar home systems that cater to off-grid households. Through flexible payment plans, Azuri Technologies has made solar power accessible to many Nigerians who were previously reliant on costly and polluting kerosene lamps (Adwek et al, 2020;Bello and Ojoyi, 2017;Opiyo, 2019).…”
Section: Private Sector Investmentsmentioning
confidence: 99%
“…However, most informal settlements in Namibia are without electricity and other essential services that could improve residents' living conditions and social status [12]. Studies have shown that access to electricity can influence the aspirations of people living in rural and informal settlements towards a productive life [13][14][15], better education [16,17], and increased health [18][19][20]. Thus, providing electricity to informal settlements is expected to reduce poverty and indirectly contribute to the country's socio-economic development.…”
Section: Introductionmentioning
confidence: 99%